Klemperer on Music: Shavings from a Musician's Workbench - Klemperer, Otto; Boulez, Pierre 1925-2016; Anderson, Martin (London Toccata Press, 1986)
Otto Klemperer's conducting career covered nearly three-quarters of the twentieth century. Although he was not chiefly a man of words, he wrote frequently on music during the course of his long life, and the writings assembled in this book date from 1906 until 1971. Klemperer writes here about musicians he knew and worked with, dwelling with especial interest and respect on Gustav Mahler, who was a formative influence on the young Klemperer. There are pieces on composers from Bach and Beethoven to Schoenberg and Zemlinsky, and on colleagues from Beecham and Toscanini to Ewald Dülberg and Max Reinhardt. He also documents his own career, discussing his conducting, his battle to save the Kroll Opera in Berlin, his period at Los Angeles, his return to Germany, his compositions, and much more.A great deal of the book has never been published before in English, and some sections appear for the first time in any language.
Keywords: Music history